2007
DOI: 10.2350/07-01-0216.1
|View full text |Cite
|
Sign up to set email alerts
|

Achondrogenesis

Abstract: In this issue of Pediatric and Developmental Pathology, Aigner and colleagues report a detailed investigation of cartilage matrix changes in a 14-week fetus with achondrogenesis type IA. The changes reported differ from matrix alterations observed in achondrogenesis types IB or II and provide insight into the phenotypic and genotypic differences within this group of skeletal dysplasias.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 7 publications
0
5
0
2
Order By: Relevance
“…Over several decades, owing to the considerable phenotypic variability, achondrogenesis type I and II have been distinguished based on clinical, radiologic, and histopathological features [10]. In our experience with the prenatal sonographic diagnosis of achondrogenesis, the fetal femur length was the best biometric parameter to distinguish achondrogenesis from other skeletal dysplasias.…”
Section: Discussionmentioning
confidence: 93%
“…Over several decades, owing to the considerable phenotypic variability, achondrogenesis type I and II have been distinguished based on clinical, radiologic, and histopathological features [10]. In our experience with the prenatal sonographic diagnosis of achondrogenesis, the fetal femur length was the best biometric parameter to distinguish achondrogenesis from other skeletal dysplasias.…”
Section: Discussionmentioning
confidence: 93%
“…The diagnosis can also be established by sequencing. For patients with ACG2, mutations are found in COL2A1 6,10 ; in ACG1B, in the DTDST gene 3,5,9,[12][13][14][15][16][17] . In the search for an implicated gene for ACG1A, Smits et al 13 found that mice with GMAP-210 deficiency died with a phenotype similar to ACG1A.…”
Section: Discussionmentioning
confidence: 99%
“…These three variants are lethal in utero. Radiological and histopathological characteristics enable differential diagnosis; between types I and II it is easier, since they are clinically different [3][4][5][6] .The present work aims to be the first report of a new ACG1A subtype with a previously unreported mode of inheritance, which is not autosomal recessive, as well as some not previously observed histopathological findings.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…As with other lethal infantile bone dysplasias, diagnosis of this spectrum can usually be made by radiography alone in the clinical setting, and an expensive molecular confirmation is of little value [5]. At the histological level, the diagnosis is supported by the demonstration of chondrocytes containing ballooned lacunae in the zones of endochondrial ossification [12].…”
Section: Discussionmentioning
confidence: 99%